CANOIL PURANUT (ENVIRONMENTALLY FRIENDLY PURWACENG LEMONGRASS AND COCONUT AROMATHERAPY CANDLE AS A SOLUTION TO INSOMNIA - vianni, tri adita; Budiati, Aprilia; Listiana, Revi; Nur Rizki, Auli Elfina; Sajid, Arkhan Ashimudin; Amania, Nila (Sentra Kekayaan Intelektual dan Inovasi Teknologi (INOTEK) Universitas Sains Al-Qur'an, 2024)
The problem of people in Indonesia today, especially adolescents, namely work stress that affects sleep patterns or called insomnia, has increased significantly. Based on research reported the prevalence of Insomnia in adolescents in Indonesia is 38% for adolescents in Urban areas and 37.7% in Suburban areas. However, this study used self-report instrument and cross-sectional method. Meanwhile, a more recent study showed that the prevalence of insomnia sufferers aged ≥19 years in Indonesia was 43.7%. Seeing these problems and realizing the opportunities that exist, aromatherapy candles are needed. Alternative medicine with the use of aroma therapy candles that are lit will produce a calming fragrance that can relieve stress. innovation in creative product activities through the manufacture of CANOILPURANUT (Aromatherapy Candles Purwaceng, Lemongrass and Coconut that are Environmentally Friendly) as a solution to work stress therapy that affects sleep patterns with treatment that is more concise and has no negative side effects to be used as a promising and sustainable business opportunity